Hautamäki, Antti. Viewpoint Relativism: a new approach to epistemological relativism based on the concept of points of view. Suiza: Springer, Synthese Library 419, 2020, 210 pp. - Brugnami, Enrico (THÉMATA. Revista de Filosofía, 2021)
Reseña de la obra "Viewpoint Relativism: a new approach to epistemological relativism based on the concept of points of view" de Antti Hautamäki